3D local directional patterns for early diagnosis of Alzheimer's disease. Issue 14 (6th February 2019) - Yan, Shiju; Song, Chengli; Zheng, Bin
Abstract : We propose a three‐dimensional‐local directional pattern (3D‐LDP) computation method in this study for early diagnosis of Alzheimer's disease. The proposed 3D‐LDP is defined as a 1‐bit decimal pattern which is calculated by computing and comparing edge response values in 18 directions. By concatenating three individual histograms extracted from three segmented sub‐regions of grey matter, the accuracy, sensitivity, and specificity of the proposed 3D‐LDP method were obtained as 81, 84, and 79%, respectively, comparable or even better than those of the existing 3D‐LTP method (80, 85, and 78%).